Illiberal Governmentality Dan Resistensi Akademi: Epistemic Accountability Dalam Demokrasi Indonesia Pasca Pemilu 2024 - Rizki Yanuartha (Jurnal Neo Societal, 2025)
This article analyzes the configuration of Indonesia's democracy after the 2024 election through the framework  of illiberal governmentality to understand how government rationality limits the democratic space. The goal is to identify governance mechanisms that normalize illiberal practices while exploring forms of academic resistance as a critical response to them. The approach used is qualitative with Critical Discourse Analysis (Fairclough), including text analysis, discourse practice, and social practice. Data were obtained from institutional statements, policy documents, democracy index reports, national and international media coverage, and NGO reports. Thematic analysis was carried out by tracing  the main frame, the relationship between discourses, and the dominant narrative regarding state relations and academic resistance, with validity strengthened through source triangulation and documentation trail audits. The results of the study show that the state maintains electoral legitimacy through electoral success, but at the same time narrows the substance of democracy through three mechanisms: (1) security channels based on legal regulations, apparatus, and digital surveillance; (2) normalization pathways through campus bureaucratization and research regulations; and (3) biopolitical pathways in the management of social assistance and digital surveillance. Academic resistance emerged as  a practice of counter governmentality based on epistemic accountability. In conclusion, the quality of Indonesia's democracy lies in the dialectic between the rationality of government and the resistance of civil society as the guardian of substantive democracy